Ethnicity, gender, and high school dropouts : a case study - Chappell, Marquessa LaBrett (2011)
High school dropout, or early school withdrawal, is a complex problem that can result from factors in all life domains. Specific factors commonly cited throughout literature in association with early school withdrawal include socioeconomic status, school mobility, and grade retention among others. There is also evidence suggesting that the factors influencing the decision to drop out of school for African American and Hispanic students may differ from the factors that influence White students. Research is conflicting as to specific gender differences among high school dropouts and with regard to the factors that influence such a decision between males and females. This study examined differences in self-reported reasons for prematurely withdrawing from school between minority status (African American and Hispanic) and non-minority status (White) students, as well as between males and females. An additional focus of this study was on school mobility and grade retention as they relate to minority status and impact high school dropout. Results indicate no significant results with regard to: minority status and high school dropout, minority status and factors related to high school dropout, school mobility and minority status, grade retention and minority status, or gender and factors related to high school dropout. However, as hypothesized, within this sample of high school dropouts, there was a significantly higher proportion of males, students who have experienced school mobility and students who have been retained. These findings support much of the research which suggests that males tend to drop out of school at a higher rate than females and that both school mobility and grade retention are plausible predictors of high school dropout. However, no support was provided for minority status as being a significant factor